Fluorine-containing polymer with functionalized side groups, preparation method of fluorine-containing polymer, ion exchange membrane and application
Through the preparation method of side group functionalized fluoropolymer, the problems of harsh reaction conditions and low yield in the prior art are solved, the grafting rate and high-temperature electrochemical properties of the polymer are improved, and it is suitable for high-efficiency ion exchange membrane materials. .
Patent Information
- Application Number
- CN202411533067.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-07
AI Technical Summary
In the prior art, when preparing perfluoro-backbone sulfonimide functionalized polymers, the reaction conditions are harsh, the comonomer polymerization rate is low, the graft reaction yield is low, and the oxidation stability of the phenyl structure is insufficient, which affects high temperature. Electrochemical properties.
The preparation method of side-functionalized fluoropolymer is adopted. The sulfonamide resin reacts with functionalized reagents in a solvent, and the organic alkali is added to maintain alkalinity. The grafting rate and yield are improved through nucleophilic substitution reactions, and high resistance is used. Substituents improve the chemical stability of the polymer.
It improves the grafting rate and electrochemical properties of the polymer, enhances the ion transport capability at high temperatures, and is suitable for ion exchange membrane materials for fuel cells, water electrolytics and flow batteries.
Smart Images

Figure CN119264303A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polymer materials, and in particular to a side-functionalized fluorine-containing polymer, a preparation method of the fluorine-containing polymer, an ion exchange membrane and applications. Background Art
[0002] Perfluorosulfonic acid resin and its membrane materials have been widely used in fuel cell proton exchange membrane and membrane electrode, chlor-alkali industrial diaphragm, flow battery diaphragm, water electrolysis hydrogen production proton exchange membrane and other fields, but its high temperature performance is poor. Sulfonyl imide functional group has excellent gas phase acidity, sulfonyl imide functionalized polymer has the advantages of good thermal stability and strong proton transport capacity, and has better electrochemical performance at high temperature than sulfonic acid functionalized polymer.
[0003] At present, sulfonyl imide functionalized polymers with perfluorinated main chains are prepared by monomer copolymerization or grafting modification to improve their thermal stability. However, the monomer copolymerization method has harsh synthesis conditions, low reactivity rate of strongly acidic comonomers, and serious corrosion to the reaction system. The grafting modification method is to react the functionalizing agent with the sulfonyl fluoride resin or sulfonamide resin with perfluorinated main chain in a solvent to obtain the target product, but the sulfonyl fluoride resin with perfluorinated main chain suitable for ion exchange membrane materials cannot be completely dissolved in fluorocarbon solvents. During the grafting process, a part of the sulfonyl fluoride resin reacts with the functionalizing agent in a swollen state, resulting in incomplete reaction of the sulfonyl fluoride group and low reaction yield. In addition, the side chain end group of some perfluorinated main chain ion exchange resins is phenyl, and the oxidative stability of the phenyl structure needs to be improved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent.
[0005] To this end, embodiments of the present invention provide a side-functionalized fluorine-containing polymer, a preparation method of the fluorine-containing polymer, an ion exchange membrane and applications.
[0006] In the first aspect, the present invention provides a side-functionalized fluorinated polymer, the structural formula of which is shown in formula (1):
[0007]
[0008] Wherein, M is selected from hydrogen, ammonium ion or metal ion;
[0009] R0 is selected from OM or NH2;
[0010] R1 is selected from alkylene, fluoroalkylene or direct bond;
[0011] R2, R3, R4, R5 and R6 are each independently selected from H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, nitrile, and at least one of them is not H;
[0012] a is an integer of 0 to 6, b is an integer of 2 to 5, and the grafting rate z of the sulfonimide group is greater than 0.1%.
[0013] Where x determines the ion exchange equivalent weight (EW) of the polymer; and y determines the molecular weight of the polymer.
[0014] In some embodiments, the grafting rate is above 1%.
[0015] In some embodiments, the grafting rate is above 5%. The higher the grafting rate, the higher the proportion of the side chains containing sulfonimide groups.
[0016] In some embodiments, R1 is selected from methylene, ethylene, propylene, butylene, perfluoromethylene, perfluoroethylene, CH(CH3), or a direct bond.
[0017] In some embodiments, R1 is selected from methylene or a direct bond.
[0018] In some embodiments, R2, R3, R4, R5 and R6 are each independently selected from H, methyl, ethyl, n-propyl, cyclohexyl, isopropyl, n-butyl, tert-butyl, phenylene, phenyl, 4-fluorophenyl, 4-methylphenyl, trifluoromethyl, pentafluoroethyl, F, and at least one is not H.
[0019] In some embodiments, R2, R3, R4, R5 and R6 are each independently selected from methyl, isopropyl, tert-butyl, phenyl, trifluoromethyl, F.
[0020] In some embodiments, R2, R3, R4, R5 and R6 are each independently selected from trifluoromethyl, fluoro.
[0021] In some embodiments, the terminal structure of the fluorinated polymer Select from the following structures:
[0022]
[0023] Isopropyl, phenyl and tert-butyl have large steric hindrance and can improve the free radical resistance of the polymer side chain end groups; F and trifluoromethyl as substituents of the benzene ring can improve the chemical stability and electrochemical properties of the polymer.
[0024] In some embodiments, the terminal structure of the fluorinated polymer The group is selected from 3-fluorophenyl, 4-fluorophenyl, 3,5-difluorophenyl, 2,6-difluorophenyl, 2,5-difluorophenyl, 2-(trifluoromethyl)phenyl, 2-fluoro-5-(trifluoromethyl)phenyl, 3-(trifluoromethyl)phenyl, 4-(trifluoromethyl)phenyl, 3,5-bis(trifluoromethyl)phenyl, 2,5-bis(trifluoromethyl)phenyl, 2,3,4,5,6-pentafluorophenyl, 2,4,6-trifluorophenyl, 2,3,5,6-tetrafluorophenyl. The group is further preferably selected from 4-fluorophenyl, 4-(trifluoromethyl)phenyl, and 2,3,4,5,6-pentafluorophenyl.
[0025] Fluorine-containing substituents can significantly improve the chemical stability of fluorine-containing polymers. In terms of the positional distribution of substituents, end groups with good symmetry have better chemical stability.
[0026] Furthermore, the metal ions include ions of at least one metal selected from the group consisting of lithium, sodium, potassium, rubidium, cesium, alkaline earth metals, iron, vanadium, titanium, silver, cerium, zinc, and manganese.
[0027] Furthermore, the EW of the fluorine-containing polymer is 450 to 2000 g / mol.
[0028] In some embodiments, the fluoropolymer has an EW of 600 to 1500 g / mol.
[0029] In some embodiments, the fluoropolymer has an EW of 700 to 1200 g / mol.
[0030] If the EW of the fluoropolymer is too high, the ion exchange capacity (IEC) of the material is low, the ion exchange capacity and ion transport capacity are poor, and the electrochemical performance when applied to proton exchange membranes or membrane electrodes is poor; if the EW of the fluoropolymer is too low, the water absorption and swelling of the material is difficult to control, and excessive water absorption and swelling will sharply reduce the dimensional stability and mechanical properties of the material.
[0031] In the second aspect, the present invention provides a method for preparing the fluorine-containing polymer provided in the first aspect of the present invention, which is obtained by reacting a sulfonamide resin with a functionalizing agent in a solvent, and an organic base is added during the reaction to keep the reaction system alkaline. The synthetic route is as follows:
[0032]
[0033] Wherein, X is selected from F, Cl, Br or I; a is an integer of 0 to 6; b is an integer of 2 to 5; and x is 2 to 10.
[0034] In some embodiments, X is selected from F and Cl, and the sulfonyl fluoride compounds and sulfonyl chloride compounds have high reactivity with the sulfonamide resin.
[0035] Further, the following steps are included:
[0036] (S1) dispersing a fluorine-containing polymer raw material in a first medium to obtain a fluorine-containing polymer raw material dispersion;
[0037] (S2) dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution;
[0038] (S3) mixing the fluorine-containing polymer raw material dispersion liquid with the functionalizing agent solution, adding an organic base to obtain a reaction dispersion liquid, and obtaining a fluorine-containing polymer crude product dispersion liquid through a nucleophilic substitution reaction;
[0039] (S4) pouring the crude product dispersion into an acid solution for acidification to obtain a crude product solid, washing the crude product solid with a third organic medium, dispersing the solid in water and / or a fourth organic medium, and filtering to obtain a fluorine-containing polymer solution;
[0040] (S5) directly drying the fluorine-containing polymer solution to obtain a fluorine-containing polymer solid or an ion exchange membrane; or, pouring the fluorine-containing polymer solution into a poor solvent for precipitation, and drying to obtain a fluorine-containing polymer solid.
[0041] Furthermore, the polymer raw material includes the sulfonamide resin shown in formula (2).
[0042] In some embodiments, the sulfonamide resin is obtained by reacting a sulfonyl halide resin with ammonia at low temperature.
[0043] Furthermore, in step (S1), the fluorine-containing polymer raw material dispersion is a fluorine-containing polymer raw material swollen in a solvent, a solution consisting of the fluorine-containing polymer raw material and the solvent, or an emulsion consisting of the fluorine-containing polymer raw material and the solvent.
[0044] Furthermore, in step (S1), the mass fraction of the fluorine-containing polymer raw material in the fluorine-containing polymer raw material dispersion is 0.1% to 30%.
[0045] In some embodiments, the mass fraction of the fluorine-containing polymer raw material in the fluorine-containing polymer raw material dispersion is 0.5% to 20%.
[0046] In some embodiments, the mass fraction of the fluorine-containing polymer raw material in the fluorine-containing polymer raw material dispersion is 1% to 20%.
[0047] The mass content of the fluorinated polymer raw material in the fluorinated polymer raw material dispersion is too low, too much solvent is consumed, and the mass content is too high, making it difficult to disperse evenly.
[0048] Furthermore, the mass ratio of the fluorine-containing polymer raw material, the functionalizing agent and the organic base in the reaction dispersion is 100:(1-300):(1-250).
[0049] In some embodiments, the mass ratio of the fluorine-containing polymer raw material, the functionalizing agent, and the organic base in the reaction dispersion is 100:(10-200):(10-150).
[0050] In some embodiments, the mass ratio of the fluorine-containing polymer raw material, the functionalizing agent, and the organic base in the reaction dispersion is 100:(30-150):(30-120).
[0051] Furthermore, the ratio of the sum of the masses of the first organic medium, the second organic medium and the organic base to the sum of the masses of the fluorine-containing polymer raw material and the functionalizing agent in the reaction dispersion is 100:(1-60).
[0052] In some embodiments, the ratio of the sum of the mass of the first organic medium, the second organic medium, and the organic base to the sum of the mass of the fluorinated polymer raw material and the functionalizing agent in the reaction dispersion is 100:(3-40).
[0053] In some embodiments, the ratio of the sum of the mass of the first organic medium, the second organic medium, and the organic base to the sum of the mass of the fluorinated polymer raw material and the functionalizing agent in the reaction dispersion is 100:(5-30).
[0054] Furthermore, the temperature of the nucleophilic substitution reaction is 50-180°C.
[0055] In some embodiments, the temperature of the nucleophilic substitution reaction is 60-180°C.
[0056] In some embodiments, the temperature of the nucleophilic substitution reaction is 80-180°C.
[0057] The reaction temperature is not higher than the boiling point of each component in the first organic medium, the second organic medium, the functionalizing agent and the organic base mixture, and the reaction system is reacted at a higher temperature by condensation reflux. The increase in temperature is conducive to accelerating the reaction rate and reducing the reaction time. When reacting in a pressure vessel, the reaction temperature is increased by increasing the pressure in the vessel. In some embodiments, the reaction pressure is 0.1 to 10 MPa, and the reaction pressure can be 0.1 MPa, 1 MPa, 5 MPa, 10 MPa or a value within the range of any two values.
[0058] Furthermore, the nucleophilic substitution reaction time is 1 to 120 hours.
[0059] In some embodiments, the nucleophilic substitution reaction time is 12 to 96 hours.
[0060] In some embodiments, the nucleophilic substitution reaction time is 18 to 72 hours.
[0061] The reaction rates of fluorinated polymer raw materials and functionalized reagents at different temperatures are different, and sufficient reaction time can improve the degree of reaction. If the reaction time is too short, the degree of reaction is low and the grafting rate of the product is low; if the reaction time is too long, the degree of reaction is basically unchanged and the grafting rate will not be further improved.
[0062] Furthermore, the acid solution includes at least one of sulfuric acid solution, nitric acid solution, phosphoric acid solution and hydrochloric acid, and the concentration thereof is above 1 mol / L.
[0063] In some embodiments, the acid solution is a hydrochloric acid solution.
[0064] In some embodiments, the acid concentration is 2-24 mol / L.
[0065] In some embodiments, the acid concentration is 4-12 mol / L.
[0066] In some embodiments, the acid solution is a 4 mol / L hydrochloric acid solution, a 6 mol / L hydrochloric acid solution, a 12 mol / L hydrochloric acid solution, etc. The side-functionalized fluoropolymer is hydrophilic, and a too low acid concentration may cause part of the product to dissolve in the acid solution, while the common ion effect between the high concentration acid solution and the fluoropolymer will cause the fluoropolymer to be fully precipitated and acidified.
[0067] In some embodiments, the acidification temperature is 20-100°C, and the acidification temperature can be 20°C, 25°C, 30°C, 50°C, 100°C, or a value within a range consisting of any two values.
[0068] In some embodiments, the acidification time is 1 to 48 hours.
[0069] Furthermore, the solid content of the fluorine-containing polymer solution is 0.5% to 40%.
[0070] In some embodiments, the solid content of the fluoropolymer solution is 2% to 20%. If the solid content of the fluoropolymer solution is too low, the solvent consumption will be too large, and if the solid content is too high, the solution viscosity will increase, which is not conducive to filtering and removing insoluble impurities.
[0071] Furthermore, the volume ratio of the poor solvent to the fluorine-containing polymer solution is 2-5.
[0072] In some embodiments, in step (S5), the drying method can be freeze drying, forced air drying or vacuum drying.
[0073] Furthermore, the first organic medium includes at least one of acetonitrile, toluene, xylene, carbitol, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetramethyl sulfoxide, hexamethylphosphoric triamide, N-methylpyrrolidone (NMP), and tetrahydrofuran.
[0074] In some embodiments, the first organic medium includes at least one of acetonitrile, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, DMSO, DMF, DMAc, and NMP.
[0075] In some embodiments, the first organic medium includes at least one of acetonitrile, dioxane, DMSO, DMF, DMAc, and NMP.
[0076] Sulfonamide resin has better solubility than sulfonyl fluoride resin and can be dissolved in fluorocarbon solvents and non-fluorine solvents. Fluorocarbon solvents are highly toxic and polluting, while non-fluorine solvents are relatively less toxic, less costly, and less polluting, and are more suitable dispersion media.
[0077] Furthermore, the second organic medium includes at least one of acetonitrile, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethyl sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone (NMP), and tetrahydrofuran.
[0078] In some embodiments, the second organic medium is selected from at least one of DMSO, DMF, DMAc, and NMP.
[0079] The functionalizing agent and the second organic medium can be mixed in any proportion. In some embodiments, the mass fraction of the functionalizing agent in the functionalizing agent solution is 1% to 80%.
[0080] In some embodiments, the mass fraction of the functionalizing agent in the functionalizing agent solution is 10% to 60%.
[0081] In some embodiments, the mass fraction of the functionalizing agent in the functionalizing agent solution is 10% to 40%.
[0082] In some embodiments, when the first organic medium is selected from the second organic medium, the functionalizing agent can be directly added to the fluorine-containing polymer raw material dispersion in step (S1).
[0083] In some embodiments, the melting point of the functionalizing agent is lower than 30° C., and the functionalizing agent can be directly added to the fluorine-containing polymer raw material dispersion in step ( S1 ).
[0084] Furthermore, the functionalizing agent includes a small molecule sulfonyl halide compound shown in formula (2).
[0085] In some embodiments, the functionalizing agent is selected from a small molecule sulfonyl chloride compound or a small molecule sulfonyl fluoride compound.
[0086] In some embodiments, the sulfonyl chloride compound is selected from 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2,3-difluorobenzenesulfonyl chloride, 2,4-difluorobenzenesulfonyl chloride, 2,5-difluorobenzenesulfonyl chloride, 2,6-difluorobenzenesulfonyl chloride, 3,4-difluorobenzenesulfonyl chloride, 3,5-difluorobenzenesulfonyl chloride, 2,3,4-trifluorobenzenesulfonyl chloride, 2,3,5-trifluorobenzenesulfonyl chloride, 2,4,5-trifluorobenzenesulfonyl chloride, 2,3,6-trifluorobenzenesulfonyl chloride, 2,4,6-trifluorobenzenesulfonyl chloride, 3,4,5-trifluorobenzenesulfonyl chloride, Fluorobenzenesulfonyl chloride, 2,3,5,6-tetrafluorobenzenesulfonyl chloride, pentafluorobenzenesulfonyl chloride, 2-(trifluoromethyl)benzenesulfonyl chloride, 3-(trifluoromethyl)benzenesulfonyl chloride, 4-(trifluoromethyl)benzenesulfonyl chloride, 2,5-bis(trifluoromethyl)benzenesulfonyl chloride, 3,5-bis(trifluoromethyl)benzenesulfonyl chloride, o-methylbenzenesulfonyl chloride, m-methylbenzenesulfonyl chloride, p-methylbenzenesulfonyl chloride, 2,6-dimethylbenzenesulfonyl chloride, 3,5-dimethylbenzenesulfonyl chloride, 2,4,6-trimethylbenzenesulfonyl chloride, 3,4,5-trimethylbenzenesulfonyl chloride, 2,3, 5,6-Tetramethylbenzenesulfonyl chloride, 4-ethylbenzenesulfonyl chloride, 4-propylbenzenesulfonyl chloride, 4-tert-butylbenzenesulfonyl chloride, 2,4,6-triisopropylbenzenesulfonyl chloride, 2-naphthalenesulfonyl chloride, 4-methyl-1-naphthalenesulfonyl chloride, 5,6,7,8-tetrahydro-2-naphthalenesulfonyl chloride, 4-biphenylsulfonyl chloride, biphenyl-2-sulfonyl chloride, 4′-fluorobiphenyl-4-sulfonyl chloride, 2-cyanobenzenesulfonyl chloride, 4-cyanobenzenesulfonyl chloride, 2-fluoro-3-methylbenzenesulfonyl chloride, 2-fluoro-4-methylbenzenesulfonyl chloride, 2-fluoro-5-methylbenzenesulfonyl chloride, At least one of 2-fluoro-5-cyanobenzenesulfonyl chloride, 3-cyano-4-fluorobenzenesulfonyl chloride, 4-fluoro-3-(trifluoromethyl)benzenesulfonyl chloride, 4-fluoro-2-(trifluoromethyl)benzenesulfonyl chloride, 5-fluoro-2-(trifluoromethyl)benzenesulfonyl chloride, o-trifluoromethylbenzylsulfonyl chloride, 3-(trifluoromethyl)benzylsulfonyl chloride, 4-methylbenzylsulfonyl chloride, 2-(1-naphthyl)ethanesulfonyl chloride, (3-methylphenyl)methanesulfonyl chloride, 4-fluorophenylmethanesulfonyl chloride, (3,5-difluorophenyl)methanesulfonyl chloride and 2-phenyl-ethanesulfonyl chloride.
[0087] In some embodiments, the sulfonyl chloride compound is selected from 2-fluorobenzenesulfonyl chloride, 3-fluorobenzenesulfonyl chloride, 4-fluorobenzenesulfonyl chloride, 2,3-difluorobenzenesulfonyl chloride, 2,4-difluorobenzenesulfonyl chloride, 2,5-difluorobenzenesulfonyl chloride, 2,6-difluorobenzenesulfonyl chloride, 3,4-difluorobenzenesulfonyl chloride, 3,5-difluorobenzenesulfonyl chloride, 2,3,4-trifluorobenzenesulfonyl chloride, 2,3,5-trifluorobenzenesulfonyl chloride, 2,3,6-trifluorobenzenesulfonyl chloride, 2,4,6-trifluorobenzenesulfonyl chloride, 3,4,5-trifluorobenzenesulfonyl chloride, 2 , at least one of 3,5,6-tetrafluorobenzenesulfonyl chloride, pentafluorobenzenesulfonyl chloride, 2-(trifluoromethyl)benzenesulfonyl chloride, 3-(trifluoromethyl)benzenesulfonyl chloride, 4-(trifluoromethyl)benzenesulfonyl chloride, 2,5-bis(trifluoromethyl)benzenesulfonyl chloride, 3,5-bis(trifluoromethyl)benzenesulfonyl chloride, 4-fluoro-3-(trifluoromethyl)benzenesulfonyl chloride, 4-fluoro-2-(trifluoromethyl)benzenesulfonyl chloride, 5-fluoro-2-(trifluoromethyl)benzenesulfonyl chloride, o-trifluoromethylbenzenesulfonyl chloride and 3-(trifluoromethyl)benzenesulfonyl chloride.
[0088] In some embodiments, the sulfonyl chloride compound is selected from at least one of 4-fluorobenzenesulfonyl chloride, 4-(trifluoromethyl)benzenesulfonyl chloride, and pentafluorobenzenesulfonyl chloride.
[0089] The corresponding sulfonyl fluoride compound can be obtained by replacing the sulfonyl chloride group of the sulfonyl chloride compound with a sulfonyl fluoride group, for example, benzenesulfonyl chloride corresponds to benzenesulfonyl fluoride, and 3-fluorobenzenesulfonyl chloride corresponds to 3-fluorobenzenesulfonyl fluoride. The scope of the sulfonyl fluoride compound is consistent with that of the corresponding sulfonyl chloride compound, and will not be repeated here.
[0090] In some embodiments, the sulfonyl fluoride compound includes at least one of 4-fluorobenzenesulfonyl fluoride, 4-(trifluoromethyl)benzenesulfonyl fluoride, and pentafluorobenzenesulfonyl fluoride.
[0091] Furthermore, the organic base includes at least one of an organic amine containing no nitrogen heterocycle and a nitrogen heterocyclic compound. 20 Alkyl and / or C6~C 20 At least one of the organic amines containing no nitrogen heterocyclic ring substituted with an aromatic group; the nitrogen heterocyclic compound includes C1 to C 20 Alkyl and / or C6~C 20 At least one of pyridine, imidazole, pyrrole, piperidine or piperazine substituted with an aromatic group.
[0092] Taking into account the reaction efficiency and the cost of the organic base, in some embodiments, a tertiary amine is used as the organic base of the reaction system.
[0093] In some embodiments, the organic base is selected from at least one of triethylamine, tripropylamine, triisopropylamine, tributylamine, tripentylamine, trihexylamine, triphenylamine, dodeca-tertiary amine, octadec-tertiary amine, N,N-dimethylcyclohexylamine, N,N-dimethylethylenediamine, N,N-diethylethylenediamine, N,N-dibutylethylenediamine, N,N-dimethylhexylamine, triethylethylenediamine, tetramethylethylenediamine, tetramethyl-1,3-propylenediamine, tetramethyl-1,6-hexanediamine, 2,5-dimethyl-p-phenylenediamine, N,N'-dibutylphenylenediamine, and N,N-dimethyldipropylenetriamine.
[0094] In some embodiments, the organic base is selected from at least one of triethylamine, tripropylamine, triisopropylamine, tributylamine, or trihexylamine.
[0095] Furthermore, the third organic medium includes at least one of fatty alcohols, lipids, fatty acids, ketones, and tetrahydrofuran, and the third organic medium is used to wash and remove excess acid in the crude product solid.
[0096] In some embodiments, the third organic medium is selected from at least one of methanol, ethanol, isopropanol, n-propanol, formic acid, acetic acid, ethyl acetate, acetone, butanone, methyl isobutyl ketone, cyclohexanone, isophorone, diacetone, and tetrahydrofuran.
[0097] In some embodiments, the third organic medium is selected from at least one of acetone and butanone. Acetone and butanone have controllable costs, are poor solvents for fluorinated polymers, do not dissolve the product, are miscible with the acid solution in any proportion, and can efficiently and thoroughly purify the product.
[0098] Furthermore, the fourth organic medium includes at least one of fatty alcohol, fatty acid, ethylene glycol, propylene glycol, glycerol, DMF, DMSO, DMAc, tetramethyl sulfoxide, tetrahydrofuran, hexamethylphosphoric acid triamide, and NMP.
[0099] In some embodiments, the fourth organic medium is selected from at least one of methanol, ethanol, n-propanol, isopropanol, n-hexanol, formic acid, acetic acid, DMF, DMSO, DMAc, tetrahydrofuran, or NMP.
[0100] In some embodiments, the fourth organic medium is selected from at least one of ethanol, n-propanol, isopropanol, DMF, DMSO, and DMAc.
[0101] Ethanol, n-propanol, isopropanol, DMF, DMSO or DMAc can fully dissolve fluoropolymers to form solutions or mixed media after mixing with water can fully dissolve fluoropolymers to form solutions. High boiling point solvents such as polyols and NMP can also fully dissolve fluoropolymers, but the higher boiling point makes the solution slightly more difficult to dry. Fatty acids such as formic acid and acetic acid have slightly stronger adsorption in fluoropolymers, making drying slightly more difficult.
[0102] Furthermore, the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones, and halogenated hydrocarbons.
[0103] In some embodiments, the poor solvent is selected from at least one of ethyl acetate, toluene, n-hexane, n-pentane, cyclohexane, acetone, butanone, and dichloromethane.
[0104] In some embodiments, the poor solvent is selected from at least one of n-hexane, cyclohexane, acetone, and butanone.
[0105] Aromatic hydrocarbons and halogenated hydrocarbons are highly toxic; lipid solvents are easily hydrolyzed into fatty acids and fatty alcohols by the acidic effect of fluorinated polymers; acetone and butanone have good miscibility with water and also with the fourth organic medium, and are suitable poor reagents; n-hexane and cyclohexane have poor miscibility with water and high-polarity organic solvents, but their polarity is very different from that of fluorinated polymers, and they have good precipitation effects. To address the problem of poor miscibility, ketones, halogenated hydrocarbons, aromatic hydrocarbons and alkanes can be mixed as poor reagents.
[0106] In a third aspect, the present invention provides a fluorine-containing polymer prepared by the fluorine-containing polymer provided in the first aspect of the present invention or the method provided in the second aspect of the present invention.
[0107] The sulfonimide functional group of the ion exchange membrane has strong gas-phase acidity, which improves the ion transmission capacity of the material at high temperature and can improve the proton conductivity of the ion exchange membrane. It is suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis, and liquid flow battery diaphragms.
[0108] Furthermore, the ion exchange membrane has a thickness of 5 to 450 μm.
[0109] In some embodiments, the ion exchange membrane has a thickness of 6 to 300 μm.
[0110] In some embodiments, the ion exchange membrane has a thickness of 7 to 200 μm.
[0111] Furthermore, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g.
[0112] In some embodiments, the ion exchange capacity of the ion exchange membrane is 0.15 to 2.5 mmol / g.
[0113] In some embodiments, the ion exchange capacity of the ion exchange membrane is 0.2 to 2 mmol / g.
[0114] Furthermore, the ion exchange membrane also includes a reinforced porous membrane, and the reinforced porous membrane includes at least one of non-fluorinated polyolefins, fluorinated polymer materials, and aromatic polymers.
[0115] In some embodiments, the non-fluorinated polyolefin includes at least one of polyethylene, polypropylene, and ethylene-propylene copolymer.
[0116] In some embodiments, the fluorine-containing polymer material includes at least one of polytetrafluoroethylene, tetrafluoroethylene hexafluoropropylene copolymer, tetrafluoroethylene propylene copolymer, ethylene tetrafluoroethylene copolymer, tetrafluoroethylene hexafluoropropylene ethylene copolymer, polyvinylidene fluoride, vinylidene fluoride hexafluoropropylene copolymer, tetrafluoroethylene perfluoroalkyl vinyl ether copolymer, vinylidene fluoride tetrafluoroethylene hexafluoropropylene copolymer, polyvinyl fluoride, polychlorotrifluoroethylene, and ethylene chlorotrifluoroethylene copolymer.
[0117] In some embodiments, the aromatic polymer film includes at least one of polyaryletherketone, polysulfone, polyethersulfone, polyethersulfoneketone, polybenzimidazole, polyaromatic amide, polyimide, and polyetheretherketone.
[0118] The ion exchange membrane is obtained by dispersing a fluorine-containing polymer in a solvent to obtain a dispersion, and then forming and drying the solution, or forming and drying the fluorine-containing polymer solution in the preparation method according to the second aspect of the present invention.
[0119] The ion exchange membrane is obtained by solution molding and drying. The obtained ion exchange membrane has good flatness, uniform thickness distribution, and better performance; the process is simple, easy to operate, and has high production efficiency, which is convenient for wide application in industrial production. The dispersion in the preparation process can also be used to prepare coatings, hydrogels and adhesives for porous membranes such as desalination membranes and ultra / microfiltration membranes, as well as various fabrics and protective equipment such as surgical gloves, protective clothing, and sterile sheets, and has a wide range of applications.
[0120] In some embodiments, when the fluorine-containing polymer is dispersed in a solvent, the dispersion temperature is 10-240° C., the dispersion time is 0.1-24 h, the dispersion pressure is normal pressure (atmospheric pressure) to 20 MPa, and auxiliary dispersion methods such as stirring, shaking or ultrasound are used to accelerate the dispersion rate.
[0121] In some embodiments, the solvent that can be used for dispersing the fluorinated polymer includes at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol. The high boiling point organic solvent includes at least one of ethylene glycol, propylene glycol, glycerol, DMF, DMAC, DMSO, hexamethylphosphoramide, and NMP; and the lower aliphatic alcohol includes at least one of methanol, ethanol, isopropanol, n-propanol, and n-butanol.
[0122] In some embodiments, the forming method of the solution forming drying process includes at least one of casting, pouring, and coating, and the drying temperature is 20 to 180°C.
[0123] In some embodiments, when the ion exchange membrane includes a reinforced porous membrane, the dispersion is coated on one side or both sides of the reinforced porous membrane during the preparation process, and the ion exchange membrane is obtained after drying. The coating method includes at least one of dipping, blade coating, and slit coating.
[0124] In the fourth aspect, the present invention proposes the use of the fluorine-containing polymer proposed in the first aspect of the present invention or the fluorine-containing polymer prepared by the method proposed in the second aspect of the present invention or the ion exchange membrane proposed in the third aspect of the present invention in batteries, chlor-alkali industry, water electrolysis to produce hydrogen, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.
[0125] In some embodiments, the fluorinated polymer or ion exchange membrane is used in proton exchange membranes for fuel cells, flow battery membranes, polyelectrolyte membranes for the chlor-alkali industry, proton exchange membranes for water electrolysis to produce hydrogen, acidic primary battery membranes, polyelectrolytes for lithium batteries, polyelectrolytes in supercapacitors, electrodialysis membranes for metal recovery and other fields.
[0126] Compared with the prior art, the beneficial effects of the present invention are:
[0127] The present invention utilizes a functionalized reagent to react with a sulfonamide resin that is easily dispersed in a solvent to obtain a fluorine-containing polymer, thereby improving the reaction yield. The main chain of the fluorine-containing polymer is a perfluorinated structure, and the end group of the side chain is a phenyl group containing a substituent. The high steric hindrance substituent or the high electronegativity substituent improves the chemical stability of the end group.
[0128] The sulfonimide functional group contained in the ion exchange membrane prepared from the fluorine-containing polymer of the present invention has strong gas phase acidity, which improves the ion transmission capacity of the material at high temperature, thereby improving the proton conductivity of the ion exchange membrane, and is suitable for fuel cell ion exchange membranes, ion exchange membranes for water electrolysis and liquid flow battery diaphragms. BRIEF DESCRIPTION OF THE DRAWINGS
[0129] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0130] Figure 1 IR spectra of PFNA-14, PFNA-15 and D-PFNA-14F;
[0131] Figure 2 The cross-sectional SEM images of PEM-15 and D-PEM-15;
[0132] Figure 3 Polarization curves of PEM-15 and D-PEM-15. DETAILED DESCRIPTION
[0133] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0134] The beneficial effects of the present application are further illustrated below in conjunction with the examples and comparative examples. Unless otherwise specified, the test materials and reagents used in the following examples can all be obtained from commercial sources.
[0135] The porous polytetrafluoroethylene membrane (ePTFE-1) is prepared by the common biaxial stretching method: (1) 75 parts of PTFE powder (Daikin F107) and 25 parts of auxiliary oil (aviation kerosene) are mixed and stirred evenly, and then prepared into a calendered belt containing auxiliary oil after aging, blanking, pushing and extrusion; (2) The calendered belt is dried to obtain a degreased membrane, and the degreased membrane is first stretched in the MD direction and then stretched in the TD direction, and a porous polytetrafluoroethylene membrane is obtained after heat setting. The stretching multiple in the MD direction is 8 times, and the stretching multiple in the TD direction is 30 times. Among them, the mechanical force direction is MD, and the cross-section to the mechanical force direction is TD. The thickness of ePTFE-1 is 3±1.5μm, the porosity is 78.2%, and the average pore size is 276nm.
[0136] The preparation method of porous polytetrafluoroethylene membrane (ePTFE-2) is basically the same as that of ePTFE-1, except that the stretching multiple in MD direction is 7 times and the stretching multiple in TD direction is 25 times. The thickness of ePTFE-2 is 7±2μm, the porosity is 77.5%, and the average pore size is 254nm.
[0137] The preparation method of porous polytetrafluoroethylene membrane (ePTFE-3) is basically the same as that of ePTFE-1, except that the stretching ratio in MD direction is 5.5 times and the stretching ratio in TD direction is 20 times. The thickness of ePTFE-2 is 12±2μm, the porosity is 75.1%, and the average pore size is 232nm.
[0138] Preparation method of sulfonamide resin: 23g of sulfonyl fluoride resin is dispersed in 150g of acetonitrile solvent, vacuumed in a high-pressure reactor and stirred and cooled to below -20°C, ammonia gas is filled into the reactor to 0.4MPa, the temperature is raised to 5°C and reacted for 6h, and then the temperature is raised to 25°C and reacted for 18h to obtain sulfonamide resin.
[0139] Fuel cell polarization curve: The test method refers to GB / T20042.5-2022 "Proton exchange membrane fuel cell Part 5: Membrane electrode test method".
[0140] Example 1
[0141] 1 g of sulfonamide resin 1 is weighed and dissolved and dispersed in the first organic medium to obtain a sulfonamide resin solution.
[0142] A certain amount of functionalizing agent is dispersed in a certain amount of the second organic medium to obtain a functionalizing agent solution.
[0143] The sulfonamide resin solution and the functionalizing agent solution are mixed in a reaction kettle, and then a certain amount of organic base is added dropwise at 20° C. The reaction system is then heated to the reaction temperature and stirred for a certain period of time.
[0144] The sulfonamide resin solution and the functionalizing agent solution are mixed in a reaction kettle, and then a certain amount of organic base is added dropwise at 20° C. The reaction system is then heated to the reaction temperature and stirred for a certain period of time.
[0145] After the reaction is completed, the reaction system is poured into 12 mol / L concentrated hydrochloric acid to precipitate solids and acidify at 30°C for 24 hours. The acidified solid product is washed with acetone until the pH value of the washing solution reaches 6.5 to 7.5. The washed solid is dissolved in 20 mL of a water-alcohol mixed solvent (the mass ratio of water, ethanol, and isopropanol is 1:7:2), and the insoluble matter is removed by filtration to obtain a fluorinated polymer solution.
[0146] The fluoropolymer solution was poured into 60 mL of cold acetone to obtain a fluoropolymer solid precipitate, which was then vacuum dried at 45° C. for 48 h to obtain a clean fluoropolymer solid.
[0147] Sulfonamide resin 1 is obtained by reacting sulfonyl fluoride resin with ammonia, and has the structural formula:
[0148]
[0149] Table 1 shows the types and amounts of the first organic medium, the second organic medium and the organic base.
[0150] Table 2 shows the type and amount of functionalizing agent, reaction temperature and reaction time.
[0151] Table 3 shows the structural formula, EW and grafting rate of the fluorinated polymers.
[0152] Table 1:
[0153]
[0154] Table 2:
[0155]
[0156]
[0157] Table 3:
[0158]
[0159]
[0160] The sulfonamide resin is dispersed in a non-fluorine solvent to form a polymer solution, a certain amount of functionalizing agent and catalyst are added, and a nucleophilic substitution reaction is carried out under appropriate reaction conditions to graft the sulfonyl imide group. A suitable reaction system can make the grafting rate reach more than 90%, the substituent-containing benzenesulfonyl halide and the sulfonamide resin have good reaction activity, and the yield of the acid-type fluorinated polymer of all reaction systems is not less than 95%. Less functionalizing agent is added to the reaction system of PFNA-10, PFNA-11 and PFNA-12, and the grafting rate of the product is low. Adjusting the amount of functionalizing agent added can controllably adjust the grafting rate of the product, and fluorinated polymers with different structures can be prepared according to different application requirements.
[0161] Example 2
[0162] 10 g of the sulfonamide resin 1 in Example 1 was weighed and dissolved in 150 mL of anhydrous DMSO, 16.5 g of 4-trifluoromethylbenzenesulfonyl chloride was added, and 50 mL of tributylamine was added, and the mixture was stirred and mixed in an autoclave under nitrogen atmosphere for 10 min.
[0163] Use a high-pressure nitrogen bottle to pressurize the autoclave to 4MPa (25°C), raise the temperature to 100°C, the pressure in the autoclave is 5MPa, and stir the reaction for 24 hours; raise the temperature to 160°C, the pressure in the autoclave is 5.8MPa, and stir the reaction for 10 hours; raise the temperature to 180°C, the pressure in the autoclave is 6.4MPa, and stir the reaction for 2 hours.
[0164] Cool to 20°C, release the pressure in the reactor, and pour out the reaction product. Add the reaction product to 12 mol / L hydrochloric acid to precipitate the solid, filter it, and acidify it with 2 mol / L hydrochloric acid at 80°C for 24 hours. Wash the acidified solid product with butanone until the pH value of the washing liquid reaches 6.5 to 7.5. Dissolve the washed solid in 150 mL DMAc, filter and remove the insoluble matter to obtain a fluorinated polymer solution.
[0165] 10mL of fluoropolymer solution was cast into an ultra-flat petri dish, dried at 80°C for 12h, and heat treated at 160°C for 15min to obtain an ion exchange membrane PEM-200 with an average thickness of 200μm. The IEC of PEM-200 is 1.05mmol / g. The remaining fluoropolymer solution was poured into 500mL of a poor solvent (the mass ratio of dichloromethane, n-hexane, and cyclohexane was 1:1:2) to obtain a fluoropolymer solid precipitate. Clean fluoropolymer solid PFNA-13 was obtained by vacuum drying at 45°C for 72h. The grafting rate of PFNA-13 is 99.5%, the EW is 951g / mol, and the yield is 93.2%.
[0166] The structural formula of PFNA-13 is:
[0167]
[0168] Example 3
[0169] 80 mL of hexafluorobenzene and 20 mL of dioxane were mixed to obtain a mixed solvent, 10 g of sulfonamide resin 2 was added, and the mixture was stirred at 50° C. for 2 h to allow the sulfonamide resin 2 to fully swell.
[0170] 9.9 g of 4-fluorobenzenesulfonyl chloride was dissolved in 5 mL of anhydrous DMF and added to the sulfonamide resin dispersion. 6 mL of triethylamine was added dropwise at 20°C, the temperature was raised to 80°C, and the reaction was stirred for 48 hours.
[0171] After the reaction is completed, the reaction system is poured into a 2 mol / L sulfuric acid solution for acidification at 80°C for 24 hours. The acidified solid product is washed alternately with water and acetone until the pH value of the washing solution reaches 6.5 to 7.5. The washed solid is dissolved in 100 mL of DMSO, and the insoluble matter is removed by filtration to obtain a fluorinated polymer solution.
[0172] Pour 5 mL of fluoropolymer solution into an ultra-flat petri dish and dry at 140 ° C for 4 hours to obtain an ion exchange membrane PEM-100 with an average thickness of 100 μm. The IEC of PEM-100 is 0.83 mmol / g. Pour the remaining fluoropolymer solution into 500 mL of a poor solvent (the mass ratio of dichloromethane to acetone is 1:1) to obtain a fluoropolymer solid precipitate. Dry in vacuo at 45 ° C for 72 hours to obtain a clean fluoropolymer solid PFNA-14. The grafting rate of PFNA-14 is ≥99.9%, the EW is 1206 g / mol, and the yield is 95.5%.
[0173] The structural formula of sulfonamide resin 2 is:
[0174]
[0175] The structural formula of PFNA-14 is:
[0176]
[0177] Example 4
[0178] 15 g of sulfonamide resin 3 was weighed and dissolved in 100 mL of anhydrous DMAc, and 50 mL of hexafluorobenzene was added to accelerate the dissolution to form a sulfonamide resin emulsion.
[0179] 25 g of pentafluorobenzenesulfonyl chloride was dissolved and dispersed in 75 mL of anhydrous DMAc to form a functionalizing agent solution.
[0180] The functionalization reagent solution and the sulfonamide resin emulsion were stirred and mixed in a normal pressure reactor under the protection of nitrogen atmosphere, 100 mL of triethylamine was added, and the temperature was raised to react under condensation reflux. The reaction temperature was 80° C. and the reaction time was 48 hours.
[0181] After the reaction is completed, pour out the reaction product. Add the reaction product to 12 mol / L hydrochloric acid to precipitate the solid, filter it, and then acidify it at 80°C for 24 hours with 2 mol / L hydrochloric acid. Wash the acidified solid product with butanone until the pH value of the washing solution reaches 6.5-7.5. Dissolve the washed solid in 200 mL of a water-alcohol mixed solvent (the mass ratio of water, ethanol, and isopropanol is 1:2:2), and filter out the insoluble matter to obtain a fluorinated polymer solution.
[0182] 20 mL of fluoropolymer solution was coated on the release film with a scraper, dried at 90°C for 5 min, and dried at 160°C for 30 min to obtain an ion exchange membrane PEM-50 with an average thickness of 50 μm. The IEC of PEM-50 is 1.05 mmol / g. The remaining fluoropolymer solution was poured into 800 mL of a poor solvent (the mass ratio of acetone to cyclohexane was 8:2) to obtain a fluoropolymer solid precipitate. Clean fluoropolymer solid PFNA-15 was obtained by vacuum drying at 45°C for 72 h. The grafting rate of PFNA-15 is ≥99.5%, the EW is 948 g / mol, and the yield is 90.0%.
[0183] The structural formula of sulfonamide resin 3 is:
[0184]
[0185] The structural formula of PFNA-15 is:
[0186]
[0187] Example 5
[0188] Weigh 25g of PFNA-13 in Example 2 and dissolve it in a mixed solvent (water, ethanol, DMF in a mass ratio of 1:2:1) at 80°C to obtain a resin dispersion. Slit-coated on both sides of ePTFE-3, dried at 90°C for 3min, and heat treated at 160°C for 30min to obtain an ion exchange membrane PEM-4 with an average thickness of 25μm. The IEC of PEM-4 is 0.9mmol / g.
[0189] Example 6
[0190] Weigh 4.5g of PFNA-14 in Example 3 and dissolve it in 25.5g of water-alcohol mixed solvent (water, ethanol, n-propanol, isopropanol, n-butanol mass ratio is 2:1:1:1:1) at 60°C to obtain a resin dispersion. Apply it on both sides of ePTFE-1 with a scraper, dry it at 110°C for 3min, and heat treat it at 160°C for 15min to obtain an ion exchange membrane PEM-14 with an average thickness of 5μm. The IEC of PEM-14 is 0.51mmol / g.
[0191] Example 7
[0192] 4.5 g of PFNA-15 in Example 4 was weighed and dissolved in 25.5 g of a water-alcohol solvent (by mass, water: ethanol: isopropanol = 4:1:5) at 60°C to obtain a dispersion, which was slit-coated on both sides of ePTFE-2, dried at 90°C for 3 min, and heat-treated at 180°C for 10 min to obtain an ion exchange membrane PEM-15 with an average thickness of 15 μm. The IEC of PEM-15 is 0.92 mmol / g.
[0193] Comparative Example 1
[0194] Different from Example 3, the functionalizing agent is 8.4 g benzenesulfonyl chloride, and D-PEM-100 and fluorinated polymer D-PFNA-14 with an average thickness of 100 microns are obtained. The IEC of D-PEM-100 is 0.84 mmol / g, the grafting rate of D-PFNA-14 is 99.8%, the EW is 1189 g / mol, the yield is 95.3%, and the structural formula is:
[0195]
[0196] Comparative Example 2
[0197] Perfluorosulfonyl imide resin 4 is prepared by free radical copolymerization of perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer. Specifically, perfluorosulfonyl imide vinyl ether monomer and tetrafluoroethylene monomer (TFE) are continuously copolymerized in disodium hydrogen phosphate / sodium dihydrogen phosphate buffer using ammonium persulfate (0.3126 g) / sodium bisulfite (0.2838 g) as initiators.
[0198] First, 2.97 g of disodium hydrogen phosphate heptahydrate and 0.2838 g of sodium dihydrogen phosphate were fully dissolved in 260 mL of deionized water after degassing to prepare a first solution; then, 4.169 g of perfluorosulfonyl imide vinyl ether monomer was added to the first solution, and the solution was cooled to 8° C. under a nitrogen atmosphere to prepare a second solution.
[0199] The autoclave was evacuated, and after purging with nitrogen three times within 5 minutes, the initiator was added to the second solution; the second solution with the added initiator was degassed with helium for more than 20 minutes; the solution was sucked into the fully evacuated autoclave, and an appropriate amount of degassed deionized water was added so that the volume of the solution was half of the reactor. When the reactor temperature reached 10°C, TFE was added until the pressure reached 150psi and the pressure was maintained at 145-150psi by adding TFE throughout the process; finally, the filtrate was acidified with 12mol / L hydrochloric acid (200mL) to obtain a precipitated polymer, and the polymer was washed with water until the water was neutral with a pH value of 6.5-7.5, and vacuum dried at 50°C for 24h to obtain D-PFNA-14F.
[0200] The EW of D-PFNA-14F is 1200 g / mol, and the structural formula is:
[0201]
[0202] 0.5 g of D-PFNA-14F was weighed and dissolved in 4.5 mL of DMSO, and dried at 140° C. for 4 h to obtain an ion exchange membrane D-PEM-100F with an average thickness of 100 μm. The IEC of D-PEM-100F was 0.83 mmol / g.
[0203] Comparative Example 3
[0204] Different from Example 2, the functionalizing agent is 11.9 g benzenesulfonyl chloride, and D-PEM-200 and fluorinated polymer D-PFNA-13 with an average thickness of 200 μm are obtained. The IEC of D-PEM-200 is 1.13 mmol / g, the grafting rate of D-PFNA-13 is 99.4%, the EW is 883 g / mol, and the yield is 92.7%.
[0205] Comparative Example 4
[0206] Weigh 4.5g of perfluorosulfonic acid resin 2 and dissolve it in 25.5g of water-alcohol solvent (by mass, water: ethanol: isopropanol = 4:1:5) at 60°C to obtain a dispersion, slit-coat the dispersion on both sides of ePTFE-2, dry at 90°C for 3min, and heat-treat at 180°C for 10min to obtain an ion exchange membrane D-PEM-15 with an average thickness of 15μm. The IEC of D-PEM-15 is 0.91mmol / g. The EW of perfluorosulfonic acid resin is 980g / mol, and the structural formula is:
[0207]
[0208] Comparative Example 5
[0209] 80 mL of hexafluorobenzene and 20 mL of dioxane were mixed to obtain a mixed solvent, 10 g of sulfonyl fluoride resin 2 was added, and the mixture was stirred at 50° C. for 2 h to allow the sulfonyl fluoride resin 2 to fully swell.
[0210] 8.5 g of benzenesulfonamide was dissolved in 15 mL of anhydrous DMF and added to the sulfonyl fluoride resin dispersion. 6 mL of triethylamine was added dropwise at 20°C, the temperature was raised to 80°C, and the reaction was stirred for 48 hours.
[0211] After the reaction is completed, the reaction system is poured into a 2mol / L sulfuric acid solution for acidification at an acidification temperature of 80°C for 24h. The acidified solid product is washed alternately with water and acetone until the pH value of the washing solution reaches 6.5-7.5. The washed solid is dissolved in 100mL DMSO, and the insoluble matter is filtered out to obtain a fluoropolymer solution. The fluoropolymer solution is poured into 500mL of a poor solvent (the mass ratio of dichloromethane to acetone is 1:1) to obtain a fluoropolymer solid precipitate. The clean fluoropolymer solid D-PFNA-14S is obtained by vacuum drying at 45°C for 72h. The grafting rate of D-PFNA-14S is 98.9%, the EW is 1187g / mol, and the yield is 74.6%.
[0212] The repeating unit of D-PFNA-14S is the same as that of D-PFNA-14 in Comparative Example 1. Compared with Comparative Example 1, the grafting rate and yield of Comparative Example 5 are lower.
[0213] The structural formula of sulfonyl fluoride resin 2 is:
[0214]
[0215] Test Example 1
[0216] The PFNA-14 prepared in Example 3, the PFNA-15 prepared in Example 4 and the D-PFNA-14F prepared in Comparative Example 2 were subjected to infrared spectroscopy test. The test results are as follows: Figure 1 shown.
[0217] from Figure 1 It can be seen that the three are at wave number 1052cm -1 、1050cm -1 、1055cm -1 The characteristic peak of SNS group is at 1286cm, which proves that the sulfonimide group is successfully grafted onto the polymer side chain; PFNA-14 and PFNA-15 have a peak at 1286cm -1 The vibration peak of CF on the benzene ring is at 878 cm -1 The out-of-plane bending vibration peak of CH on the benzene ring is at 1600-1800cm -1 The sawtooth-shaped doublet absorption peak (doublet or group frequency absorption of CH out-of-plane and C=C in-plane bending vibration) appears at the point, which is a typical characteristic of substituted benzene.
[0218] Test Example 2
[0219] The PEM-15 prepared in Example 7 and the D-PEM-15 prepared in Comparative Example 4 were subjected to SEM tests. The test results are shown in FIG. Figure 2 shown.
[0220] from Figure 2 It can be seen that both materials have good filling effects in the reinforcement layer.
[0221] Test Example 3
[0222] The PEM-15 prepared in Example 7 and the D-PEM-15 prepared in Comparative Example 4 were subjected to a fuel cell polarization curve test at 80°C and 65% RH. The test results are shown in FIG. Figure 3 As shown, the fuel cell polarization curve test method refers to GB / T20042.5-2022 "Proton Exchange Membrane Fuel Cell Part 5: Membrane Electrode Test Method".
[0223] from Figure 3 It can be seen that under the conditions of 80°C and 65% RH, the power density of the membrane electrode prepared by PEM-15 reaches 1466mW / cm 2 @0.6V, better than D-PEM-15’s 937mW / cm 2 @0.6V, and has lower internal resistance and better fuel cell single cell performance.
[0224] Test Example 4
[0225] The water absorption, tensile strength, tensile modulus, free radical resistance and electrical conductivity of the ion exchange membranes obtained in Example 2, Example 3, Example 7 and Comparative Examples 1 to 4 were tested. The test results are shown in Tables 4 and 5.
[0226] Among them, the test methods for conductivity, EW, IEC, water absorption and mechanical properties refer to GB / T20042.3-2022 "Proton Exchange Membrane Fuel Cell Part 3: Proton Exchange Membrane Test Method".
[0227] The test method for the free radical resistance of the ion exchange membrane is: immerse the ion exchange membrane in Fenton's reagent at 80°C for 8 hours, and compare the mass loss and conductivity decay before and after immersion. The preparation process of Fenton's reagent is: add 0.1mL of Fe with a molar concentration of 0.01mol / L to 50mL of H2O2 solution with a mass fraction of 3% 2+ The solution is the Fenton reagent, which is prepared and used immediately. The smaller the mass loss percentage, the better the durability. The smaller the conductivity decay of the ion exchange membrane after the Fenton reagent treatment, the better the free radical resistance.
[0228] Table 4:
[0229]
[0230] Table 5:
[0231]
[0232] As can be seen from Table 4 and Table 5, the IEC and water absorption of PEM-100 of Example 3 are similar to those of D-PEM-100 of Comparative Example 1, but the phenyl groups on the side chains of the fluorinated polymer in PEM-100 contain strongly electronegative fluorine substituents. Such fluorine substituents themselves have good chemical stability, the hydrogen bonding effect formed between the end groups can improve the mechanical properties of the material, and the strong electronegativity can improve the acidity of the ionic group, so PEM-100 exhibits better chemical stability, mechanical strength and electrochemical properties.
[0233] Compared with D-PEM-100F of Comparative Example 2, the IEC, water absorption and conductivity under different temperature and humidity of PEM-100 of Example 3 are similar, but the end group of the fluoropolymer side chain in PEM-100 is a rigid phenyl group containing a substituent. This rigid group gives PEM-100 a higher tensile strength and tensile modulus, thereby enhancing the mechanical stability of the ion exchange membrane. Due to the weak stability of hydrogen on the phenyl group of PEM-100, its free radical resistance is slightly lower than that of D-PEM-100F with a perfluorinated structure, but the difference is small. The preparation method of D-PFNA-14F is complicated, the cost is high, the competitive polymerization rate of strong acidic monomers is low, and the application is limited.
[0234] Compared with the D-PEM-200 of Comparative Example 3, the PEM-200 of Example 2 has a higher IEC, and therefore has a higher conductivity under different temperatures and humidities. However, the terminal group of D-PEM-200 is phenyl, and its chemical stability is poor. The mass loss in the free radical resistance test is more than 3 times that of PEM-200, making it difficult to be applied to fuel cells, water electrolysis and hydrogen production and other fields.
[0235] The PEM-15 of Example 7 and the D-PEM-15 of Comparative Example 4 both contain a reinforcement layer, and the tensile strength is more than 50 MPa. The perfluorophenyl end group structure of PFNA-15 in PEM-15 effectively improves the mechanical properties and free radical resistance of the ion exchange membrane. The conductivity of PEM-15 and D-PEM-15 under high humidity conditions is similar, but under high temperature and low humidity conditions, the sulfonimide functional group of PEM-15 makes it have higher conductivity, which is more suitable for the actual working conditions of fuel cells.
[0236] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms may be for different embodiments or examples. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0237] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0238] Although the embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A side-functionalized fluorinated polymer, characterized in that The structural formula is shown in formula (1): Wherein, M is selected from hydrogen, ammonium ion or metal ion; R0 is selected from OM or NH2; R1 is selected from alkylene, fluoroalkylene or direct bond; R2, R3, R4, R5 and R6 are each independently selected from H, alkyl, cycloalkyl, fluoroalkyl, alkylene, phenyl, phenylene, F, nitrile, and at least one of them is not H; a is an integer of 0 to 6, b is an integer of 2 to 5, and the grafting rate z of the sulfonimide group is greater than 0.1%.
2. The fluorine-containing polymer according to claim 1, characterized in that The metal ions include ions of at least one metal selected from the group consisting of lithium, sodium, potassium, rubidium, cesium, alkaline earth metals, iron, vanadium, titanium, silver, cerium, zinc, and manganese.
3. The fluorine-containing polymer according to claim 1, characterized in that The EW of the fluorine-containing polymer is 450 to 2000 g / mol.
4. A method for preparing a side-functionalized fluorine-containing polymer, characterized in that: For preparing the fluorine-containing polymer as claimed in any one of claims 1 to 3, the synthesis route is as follows: Wherein, X is selected from F, Cl, Br or I; a is an integer of 0 to 6; b is an integer of 2 to 5; and x is 2 to 10.
5. The preparation method according to claim 4, characterized in that: The following steps are involved: (S1) dispersing a fluorine-containing polymer raw material in a first organic medium to obtain a fluorine-containing polymer raw material dispersion; (S2) dispersing a functionalizing agent in a second organic medium to obtain a functionalizing agent solution; (S3) mixing the fluorine-containing polymer raw material dispersion liquid with the functionalizing agent solution, adding an organic base to obtain a reaction dispersion liquid, and obtaining a fluorine-containing polymer crude product dispersion liquid through a nucleophilic substitution reaction; (S4) pouring the crude product dispersion into an acid solution for acidification to obtain a crude product solid, washing the crude product solid with a third organic medium, dispersing the solid in water and / or a fourth organic medium, and filtering to obtain a fluorine-containing polymer solution; (S5) directly drying the fluorine-containing polymer solution to obtain a fluorine-containing polymer solid or an ion exchange membrane; or, pouring the fluorine-containing polymer solution into a poor solvent for precipitation, and drying to obtain a fluorine-containing polymer solid.
6. The preparation method according to claim 5, characterized in that: The fluorine-containing polymer raw material dispersion is a fluorine-containing polymer raw material swollen in a solvent, a solution composed of the fluorine-containing polymer raw material and the solvent, or an emulsion composed of the fluorine-containing polymer raw material and the solvent; and / or, the mass fraction of the fluorine-containing polymer raw material in the fluorine-containing polymer raw material dispersion is 0.1% to 30%; and / or, the mass ratio of the fluorinated polymer raw material, the functionalizing agent, and the organic base in the reaction dispersion is 100:(1-300):(1-250); and / or, the ratio of the sum of the mass of the first organic medium, the second organic medium, and the organic base to the sum of the mass of the fluorinated polymer raw material and the functionalizing agent in the reaction dispersion is 100:(1-60); and / or, the polymer raw material comprises a sulfonamide resin as shown in formula (2); and / or, the functionalizing agent comprises a small molecule sulfonyl halide compound shown in formula (2); and / or, the temperature of the nucleophilic substitution reaction is 50 to 180° C., which is not higher than the boiling point of each component in the first organic medium, the second organic medium, the functionalizing agent and the organic base mixture; And / or, the time of the nucleophilic substitution reaction is 1 to 120 hours; And / or, the acid solution includes at least one of sulfuric acid solution, nitric acid solution, phosphoric acid solution, and hydrochloric acid, and its concentration is above 1 mol / L; And / or, the acidification temperature is 20 to 100°C; and / or, the solid content of the fluorine-containing polymer solution is 0.5% to 40%; And / or, the volume ratio of the poor solvent to the fluorine-containing polymer solution is 2-5.
7. The preparation method according to claim 5, characterized in that: The first organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, hexafluorobenzene, decafluorobiphenyl, hexafluoropropylene trimer, pentafluorophenol, perfluoromethyldecahydronaphthalene, dimethyl sulfoxide (DMSO), N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), tetramethyl sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone (NMP), and tetrahydrofuran; and / or, the second organic medium comprises at least one of acetonitrile, toluene, xylene, carbitol, dioxane, DMSO, DMF, DMAc, tetramethyl sulfoxide, hexamethylphosphoramide, N-methylpyrrolidone (NMP), and tetrahydrofuran; And / or, the organic base includes at least one of an organic amine containing no nitrogen heterocycle and a nitrogen heterocyclic compound; and / or, the third organic medium comprises at least one of fatty alcohols, lipids, fatty acids, ketones, and tetrahydrofuran; And / or, the fourth organic medium comprises at least one of aliphatic alcohol, fatty acid, ethylene glycol, propylene glycol, glycerol, DMF, DMSO, DMAc, tetramethyl sulfoxide, tetrahydrofuran, hexamethylphosphoric acid triamide, and NMP; And / or, the poor solvent includes at least one of lipids, aromatic hydrocarbons, alkanes, ketones, and halogenated hydrocarbons.
8. An ion exchange membrane, characterized in that: The fluorine-containing polymer described in any one of claims 1 to 3 or the fluorine-containing polymer prepared by any one of claims 4 to 7 is dispersed in a solvent and then solution-molded and dried, or the fluorine-containing polymer solution in step (S4) of any one of claims 5 to 7 is molded and dried.
9. The ion exchange membrane according to claim 8, characterized in that Also included is a reinforced porous membrane, wherein the reinforced porous membrane includes at least one of a non-fluorinated polyolefin, a fluorinated polymer material, and an aromatic polymer; And / or, the thickness of the ion exchange membrane is 5 to 450 μm; and / or, the ion exchange capacity of the ion exchange membrane is 0.1 to 4 mmol / g; And / or, the solvent comprises at least one of water, a high boiling point organic solvent, tetrahydrofuran, and a lower aliphatic alcohol; And / or, the forming includes at least one of casting, pouring and coating.
10. Use of the fluorinated polymer according to any one of claims 1 to 3 or the fluorinated polymer prepared by the method according to any one of claims 4 to 7 or the ion exchange membrane according to claim 8 or 9 in batteries, chlor-alkali industry, water electrolysis to produce hydrogen, capacitors, electrodialysis, sensors, desalination membranes, ultrafiltration membranes, microfiltration membranes, fabrics, and protective equipment.
Citation Information
Cited By
Perfluorosulfonyl imide type proton exchange resin with high oxygen permeability as well as preparation method and application of perfluorosulfonyl imide type proton exchange resin
CN121293422A